Quality Analysis of Signal and Attenuation of Outdoor Wi-Fi in Dynamic Weather Conditions - Yoga, I Made Gita; Sinaga, Made Sutha Yadnya; Sasongko, Sudi M. Al (International Journal of Informatics and Computation, 2026)
This paper analyzes the quality of outdoor Wi-Fi signals and rain attenuation under dynamic weather conditions using UniFi 6 Mesh and UniFi 7 Pro devices at 2.4 GHz and 5 GHz frequencies. Our proposed method evaluates network performance using QoS parameters, RSSI measurements, and theoretical rain attenuation analysis based on ITU-R propagation models. The experiments were conducted under sunny, light rain, and heavy rain conditions in a real outdoor environment at Ayana Resort Bali Hotel. The QoS results achieved excellent performance with throughput of 22.17 Mbps, packet loss of 0.015%, delay of 0.41 ms, and jitter of 0.000 ms, producing a TIPHON index value of 4 categorized as “Very Satisfactory.” The RSSI analysis showed that increasing rainfall intensity significantly reduced signal strength, especially at the 5 GHz frequency. The highest degradation occurred at the UniFi 7 Pro 5 GHz channel, where RSSI decreased from -40.80 dBm during sunny weather to -62.61 dBm during heavy rain. The results also demonstrated that actual attenuation values were much higher than theoretical attenuation due to environmental factors such as humidity, wet surfaces, and multipath propagation. This study confirms that weather conditions strongly influence outdoor Wi-Fi performance and highlights the importance of empirical field testing for reliable outdoor wireless network deployment.